1981
DOI: 10.1111/j.1348-0421.1981.tb00124.x
|View full text |Cite
|
Sign up to set email alerts
|

Biological and Biochemical Characterization of Macrophage Activating Factor (MAF) in Murine Lymphocytes: Role of Mannopyranosyl Residue of the MAF Molecule in Macrophage Activation

Abstract: Activation of macrophages with macrophage activating factor (MAF) was evaluated by measuring the intracellular killing activity of murine macrophages against Salmonella typhimurium. Concanavalin A (Con A)-induced MAFrich fraction was obtained by a Sephadex G-IOO column, which contained molecules ranging from 25,000 to 67,000 daltons. The intracellular killing ability of mouse peritoneal macrophages against S. typhimurium was found to be increased by 0.1 M D-mannose as well as by Con A-induced MAF-rich fraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

1983
1983
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…In this decade, many papers have been published on animal lectins specifically binding to N-acetyl-D-glucosamine, D-glucosamine, and D-mannose residues on the surface of phagocytic cells (2,5,19). According to the description by Oda et al (13), significant suppression of the phagocytic effects on fungal cells was observed for macrophages treated with D-mannose, D-glucosamine, and N-acetyl-D-glucosamine in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…In this decade, many papers have been published on animal lectins specifically binding to N-acetyl-D-glucosamine, D-glucosamine, and D-mannose residues on the surface of phagocytic cells (2,5,19). According to the description by Oda et al (13), significant suppression of the phagocytic effects on fungal cells was observed for macrophages treated with D-mannose, D-glucosamine, and N-acetyl-D-glucosamine in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Correspondingly, the ability of KO3 LPS to induce interleukin-1 secretion in cultures of mouse peritoneal macrophages is significantly greater than that of E. coli O127 LPS (10). Rat alveolar macrophages (21) and mouse peritoneal macrophages (2,22) are known to possess mannose-binding protein on their surface. Recently it has been shown that muramyldipeptide (MDP) activates only slightly rat or mouse alveolar macrophages in rendering tumoricidal activity and the activation of alveolar macrophages is dramatically enhanced by MDP bound to a neoglycoprotein (mannosylated bovine serum albumin) (12).…”
Section: Discussionmentioning
confidence: 99%
“…They are released by T-lymphocytes, other macrophages, and endothelial cells after activation by antigens, mitogens, or inflammatory cytokines (Fukazawa, Kagaya, & Miura, 1981). MCF attracts macrophages to migrate to the infected tissue (Handa, Mitsuyama, Serushago, Muramori, & Nomoto, 1988).…”
Section: Introductionmentioning
confidence: 98%